OPTIMALISASI PERAN MASJID DALAM PENDIDIKAN ANAK: PERSPEKTIF MAKRO DAN MIKRO - Ikhwan, Afiful (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2013)
The mosque as a instrument that can be used to prostrate, alsomeans it can be used for social activities involving humandimension by making it as a central activity. This relates also to thepotential mosque itself should be empowered with all the ability ofthe managers. In this case it takes expertise (skills) are not onlysufficient, but must be fully implemented as the implementation ofthe propaganda bi ahsan al-amal (make changes by mobilizing allabilities). With this kind of understanding, the mosque can beinterpreted as an instrument or means of universal worship. Notonly worship mahdhoh (micro), but also worship ghayro mahdhah(macro). So, mosques back again in his role as the time of ProphetMuhammad saw- before that, as an educational center that seeks toeducate the religion of Islam and its values, to become ones way oflife.